Taller Haustral Folds in the Proximal Colon: A Potential Factor Contributing to Interval Colorectal Cancer - Atalie, C. Thompson; Richard, H. Jones; Peter, D. Poullos; Subhas, Banerjee; Lewis, K. Shin (Journal of Colon And Rectal Cancer, 2016)
Missed cancers have been reported at higher frequencies in the right colon despite optical colonoscopy screening. The purpose of this study was to determine if there are regional differences in haustral fold height between the ascending, transverse, and descending colon using CT colonography (CTC). 50 supine CTC datasets from 50 asymptomatic, adult patients were analyzed (NCI-CBIIT instance of the National Biomedical Imaging Archive). At least 5 consecutive, pairs of unobscured haustral folds in each colonic segment were necessary to be included in this study. Of an initial 201 patients, 151 were excluded due to suboptimal colonic distension, retained fluid, tortuosity, and diverticulosis. For each dataset, the heights of the non-dependent haustral folds were measured in the ascending, transverse, and descending colon on 2D multiplanar reformations. Differences in mean HFHs were assessed using a hierarchical generalized linear mixed model. A total of 2079 colonic folds were measured: 625 in the ascending colon (including the cecum), 687 in the transverse colon, and 767 in the descending colon. The mean number of folds measured per segment was 6.87 ± 2.11. Mean HFHs were significantly taller in the ascending colon (14.62 ± 5.47 mm) than in the transverse (9.49 ± 3.65mm) or descending (6.53 ± 3.12mm) colon; mean HFHs were also significantly taller in the transverse than the descending colon, (P<0.0001, for all comparisons). In conclusion, taller colonic haustral folds are present in the proximal colon and may contribute to more frequently missed lesions (e.g. polyps) in the right colon by conventional, optical colonoscopy.
Keywords: Haustral Fold Heights; Computed Tomographic Colonography; Virtual Colonoscopy; Optical Colonoscopy; Colorectal Cancer Screening